2003
DOI: 10.4049/jimmunol.171.11.6173
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Immune Induction of Collagen-Induced Arthritis in IL-17-Deficient Mice

Abstract: Interleukin-17 is a T cell-derived proinflammatory cytokine. This cytokine is suspected to be involved in the development of rheumatoid arthritis (RA) because this cytokine expression is augmented in synovial tissues of RA patients. The pathogenic roles of IL-17 in the development of RA, however, still remain to be elucidated. In this study, effects of IL-17 deficiency on collagen-induced arthritis (CIA) model were examined using IL-17-deficient mice (IL-17−/− mice). We found that CIA was markedly suppressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
919
2
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,162 publications
(976 citation statements)
references
References 28 publications
43
919
2
12
Order By: Relevance
“…It was later reported that the role of IL-23 involved induction or expansion of Th17 cells; autoantigen-specific Th17 cells transferred EAE to naïve mice [22]. Furthermore, mice treated with anti-IL-17 neutralizing antibody [75] or IL-17 À/À mice [76,77] had reduced susceptibility to experimentally induced autoimmunity, though the attenuation was not as pronounced as that observed in IL-23 À/À mice. This was complemented by studies in humans, which showed that CD4 1 T cells from MS patients secrete higher levels of IL-17 than healthy donors following in vitro stimulation with plate-bound anti-CD3 [78].…”
Section: Role Of Il-17-secreting T Cells In Immune-mediated Diseasesmentioning
confidence: 97%
“…It was later reported that the role of IL-23 involved induction or expansion of Th17 cells; autoantigen-specific Th17 cells transferred EAE to naïve mice [22]. Furthermore, mice treated with anti-IL-17 neutralizing antibody [75] or IL-17 À/À mice [76,77] had reduced susceptibility to experimentally induced autoimmunity, though the attenuation was not as pronounced as that observed in IL-23 À/À mice. This was complemented by studies in humans, which showed that CD4 1 T cells from MS patients secrete higher levels of IL-17 than healthy donors following in vitro stimulation with plate-bound anti-CD3 [78].…”
Section: Role Of Il-17-secreting T Cells In Immune-mediated Diseasesmentioning
confidence: 97%
“…Il17 –/– mice show significantly reduced severity in various inflammatory and autoimmune disease models, such as collagen‐induced arthritis,6 Il1rn −/− mouse arthritis,7 EAE8 and imiquimod (IMQ)‐induced skin inflammation,9, 10 suggesting critical roles of IL‐17 in inflammatory/autoimmune diseases. γδ 17 cells are detected in inflamed tissues of these disease models.…”
Section: The Pathogenic Roles Of γδ17 Cells In Mouse Inflammatory Dismentioning
confidence: 99%
“…Mice deficient for IL‐17RA are highly susceptible to Klebsiella pneumoniae 3 and IL‐17‐deficient mice are susceptible to bacterial and fungal infection 4, 5. Interleukin‐17 is also implicated in various inflammatory/autoimmune disease models such as experimental autoimmune encephalomyelitis (EAE), arthritis in IL‐1 receptor antagonist‐deficient (Il1rn –/– ) mice and imiquimod‐induced psoriatic dermatitis in mice 6, 7, 8, 9, 10. Anti‐IL‐17 and anti‐IL‐17RA antibodies are effective to treat patients with psoriasis and psoriatic arthritis 11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…In mice deficient for the Th17 cell-associated molecules interleukin-17 (IL-17), IL-17 receptor, or IL-23p19, arthritis is markedly suppressed compared with that in their wild-type counterparts (5)(6)(7), and neutralizing antibodies to IL-17 have a therapeutic effect in CIA (8). In humans, some evidence supports the involvement of Th17 cells in the pathogenesis of RA.…”
Section: Conclusion Treatment With Type II Collagenpulsed Tolerogenimentioning
confidence: 99%